Angiotensin receptor blockade with olmesartan alleviates brain pathology in obese OLETF rats. (4th December 2022) - Rodriguez‐Ortiz, Carlos J.; Thorwald, Max A.; Rodriguez, Ruben; Mejias‐Ortega, Marina; Kieu, Zanett; Maitra, Neilabjo; Hawkins, Charlesice; Valenzuela, Joanna; Peng, Marcus; Nishiyama, Akira; Ortiz, Rudy M.; Kitazawa, Masashi
Abstract: Metabolic syndrome (MetS) is a rapidly increasing health concern during midlife and is an emerging risk factor for the development of neurodegenerative diseases, such as Alzheimer's disease (AD). While angiotensin receptor blockers (ARB) are widely used for MetS‐associated hypertension and kidney disease, its therapeutic potential in the brain during MetS are not well‐described. Here, we tested whether treatment with ARB could alleviate the brain pathology and inflammation associated with MetS using the Otsuka Long–Evans Tokushima Fatty (OLETF) rat. Here, we report that chronic ARB treatment with olmesartan (10 mg/kg/day by oral gavage for 6 weeks) partially but significantly ameliorated accumulation of oxidized and ubiquitinated proteins, astrogliosis and transformation to neurotoxic astrocytes in the brain of old OLETF rats, which otherwise exhibit the progression of these pathological hallmarks associated with MetS. Additionally, olmesartan treatment restored claudin‐5 and ZO‐1, markers of the structural integrity of the blood–brain barrier as well as synaptic protein PSD‐95, which were otherwise decreased in old OLETF rats, particularly in the hippocampus, a critical region in cognition, memory and AD. These data demonstrate that the progression of MetS in OLETF rats is associated with deterioration of various aspects of neuronal integrity that may manifest neurodegenerative conditions and that overactivation of angiotensin receptor directly or indirectly contributes to these detriments. Thus, olmesartan treatment may slow or delay the onset of degenerative process in the brain and subsequent neurological disorders associated with MetS.